Insulin signaling pathways in lepidopteran ecdysone secretion - Smith, Wendy; Lamattina, Anthony; Collins, McKensie (Frontiers in Physiology, 2014)
Molting and metamorphosis are stimulated by the secretion of ecdysteroid hormones from the prothoracic glands. Insulin-like hormones have been found to enhance prothoracic gland activity, providing a mechanism to link molting to nutritional state. In silk moths (Bombyx mori), the prothoracic glands are directly stimulated by insulin and the insulin-like hormone bombyxin. Further, in Bombyx , the neuropeptide prothoracicotropic hormone (PTTH) appears to act at least in part through the insulin-signaling pathway. In the prothoracic glands of Manduca sexta, while insulin stimulates the phosphorylation of the insulin receptor and Akt, neither insulin nor bombyxin II stimulate ecdysone secretion. Involvement of the insulin-signaling pathway in Manduca prothoracic glands was explored using two inhibitors of phosphatidylinositol-3-kinase (PI3K), LY294002 and wortmannin. PI3K inhibitors block the phosphorylation of Akt and 4EBP but have no effect on ecdysone secretion, or on the phosphorylation of the MAPkinase, ERK. Inhibitors that block phosphorylation of ERK, including the MEK inhibitor U0126, and high doses of the RSK inhibitor SL0101, effectively inhibit ecdysone secretion. The results highlight differences between the two lepidopteran insects most commonly used to directly study ecdysteroid secretion. In Bombyx, the PTTH and insulin-signaling pathways intersect; both insulin and PTTH enhance the phosphorylation of Akt and stimulate ecdysteroid secretion, and inhibition of PI3K reduces ecdysteroid secretion. By contrast, in Manduca, the action of PTTH is distinct from insulin. The results highlight species differences in the roles of translational regulators such as 4EBP, and members of the MAPkinase pathway such as ERK and RSK, in the effects of nutritionally-sensitive hormones such as insulin on ecdysone secretion and molting.